2020
DOI: 10.1002/cpt.1894
|View full text |Cite|
|
Sign up to set email alerts
|

Propranolol Suppresses the Growth of Colorectal Cancer Through Simultaneously Activating Autologous CD8+ T Cells and Inhibiting Tumor AKT/MAPK Pathway

Abstract: Propranolol suppresses tumor growth in a variety of preclinical solid tumor models, with a number of proposed cell signaling and immunological mechanisms. We want to confirm the potential mechanisms, including reduced phosphorylation of AKT/MAPK pathways, as well as enhanced CD8+ T‐cell–mediated antitumor immune response. To clarify the mechanism of propranolol activity in colorectal cancer, the therapeutic activity of propranolol was then assessed in CT26WT tumors engrafted in BALB/C mice. Then the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
(47 reference statements)
2
22
0
Order By: Relevance
“…MAPK-mutant tumors are the only CD8+ T cell-inflamed tumors with high immunoreactivity and a constitutively cytolytic tumor microenvironment. The MAPK-mutant head and neck squamous-cell carcinoma model with immune function shows active cell death and extensive CD8+ T cell recruitment (61,62). We infer that BMPR2 regulates the immune microenvironment of osteosarcoma tissue through the MAPK/ERK pathway.…”
Section: Os Sarc ----------------------------------------------------mentioning
confidence: 78%
“…MAPK-mutant tumors are the only CD8+ T cell-inflamed tumors with high immunoreactivity and a constitutively cytolytic tumor microenvironment. The MAPK-mutant head and neck squamous-cell carcinoma model with immune function shows active cell death and extensive CD8+ T cell recruitment (61,62). We infer that BMPR2 regulates the immune microenvironment of osteosarcoma tissue through the MAPK/ERK pathway.…”
Section: Os Sarc ----------------------------------------------------mentioning
confidence: 78%
“…Liao et al. also found that propranolol inhibited colorectal cancer proliferation by regulating the AKT and MAPK pathways ( 7 ). Previous studies demonstrated that propranolol can down-regulate the expression of CyclinD1, leading to G1/S arrest ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, many studies have proved that propranolol can induce apoptosis, inhibit proliferation, angiogenesis, and metastasis across solid tumors ( 2 6 ). Recent data suggested that propranolol suppressed colorectal cancer cell growth through simultaneously activating autologous CD8 + T cells and decreasing the phosphorylation level of mitogen-activated protein kinase (MAPK)/(ATP-dependent tyrosine kinases) AKT pathway ( 7 ). Several studies also observed that propranolol may exert an anti-tumor effect in melanoma and breast cancer by suppressing AKT and MAPK signaling pathways ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…[37], while other drugs in the same class, such as carvedilol and nebivolol, also have anti-cancer efficacy [38]. Propranolol has been repurposed as an anti-cancer agent due to its effects on cellular proliferation [39][40][41], migration [40], invasion [42,43], apoptosis [39,41], angiogenesis [44], treatment sensitization [41,45,46], as well as on the immune system [47][48][49][50][51][52].…”
Section: Chronic Stress and Cancermentioning
confidence: 99%